New Approach for Diagnostics of VZV Infection by Using Real-Time PCR - H. Ph. Pham; A. V. Sidorov; A. V. Milovanova; T. P. Antonova; A. N. Lisakov; F. G. Nagieva; G. I. Alatortceva; O. A. Svitich; A. C. Kasanova; V. F. Lavrov; V. V. Zverev (Эпидемиология и вакцинопрофилактика)
Clinical picture of diseases caused by VZV in immunocompromised patients is often differed from healthy people and has no visible skin damage. Diagnostics in such cases is difficult but it is important to find out real reason of health deterioration for assignment the treatment. That explains usefulness of molecular methods in diagnostics of VZV-infection. So the goal of this study was checking out usefulness of diagnostics based on detection viral DNA in clinical samples by real-time PCR method. We used pools of peripheral blood samples from sick and healthy patients as clinical materials for analysis and Varilrix vaccine sample as a source of positive control viral DNA. Main methods used here were DNA extraction and real-time PCR in the version of TaqMan probes; amplification reactions were made in triplicates for each sample with standard deviation of threshold cycles less than 1.5%. Amplification results of clinical samples from patients were analyzed by comparison with the results from positive control viral DNA. Final resulting figures were slightly varied and dependent on selected for amplification VZV genome fragment (orf 29 or orf 38), and viral DNA had been detected in 48% of sick patients and only in 4% of practically healthy donors without zoster symptoms. Concluding, we approved the possibility of use real-time PCR as a molecular method for laboratory diagnostics VZV-infection including atypical and subclinical disease forms. One of the advantage of the method described is the possibility of DNA detection straight from blood samples (without extra purification steps such as preparation mononuclear cell fraction from blood samples), therefore this approach can accelerate and simplify diagnostic procedure.